Antimicrobial activity of disinfectant agents incorporated into type IV dental stone - Pereira, Rodrigo de Paula [UNESP]; Lucas, Matheus Guilherme [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Arioli Filho, João Neudenir [UNESP] (Wiley-Blackwell, 2012)
Purpose: This study evaluated the antimicrobial activity of two disinfectant agents, 2% chlorhexidine digluconate solution (CHX) and 98% chlorhexidine hydrochloride powder (HYD), incorporated into type IV dental stone at the time of mixing.Material and methods: Agar diffusion test was used for the following microorganisms: Escherichia coli, Staphylococcus aureus, Bacillus subtilis and Candida albicans. The specimens were grouped in: (1) dental stone mixed with sterile distilled water; (2) paper disc soaked with CHX; (3) dental stone mixed with CHX; and (4) dental stone with incorporation of HYD, in 1% proportion of the dental stone mass and mixed with sterile distilled water. The culture medium was inoculated with microbial suspensions 1 and 24 h after pouring of the dental stone. The antimicrobial activity was evaluated by the average diameter of microbial growth inhibition zones. The data were analysed with a nested ANOVA (p < 0.05) and Tukey test for specific comparisons.Results: The disinfectant agents demonstrated antimicrobial activity against all microorganisms, with the exception of C. albicans, against which the CHX was ineffective in two periods of analysis. Significant differences between disinfectants were found with all microorganisms.Conclusion: The disinfectant agents analysed were effective against most of the microorganisms tested, except C. albicans.
Keywords: antimicrobial activity; chlorhexidine; infection control; disinfectant agents; calcium sulphate